Combination with Red ginseng and Polygoni Multiflori ameliorates highfructose diet induced metabolic syndrome. Issue 1 (December 2016) - Kho, Min; Lee, Yun; Park, Ji; Cha, Jeong; Choi, Kyung; Kang, Dae; Lee, Ho
Abstract Background Metabolic syndrome such as dyslipidemia, hypertension, obesity, impaired glucose tolerance and fatty liver, can be caused by modification of diet by means of overconsumption of high fructose diet. This study was designed to investigate whether combination with Red ginseng andPolygoni Multiflori Radix (RGPM), widely used traditional herbal medicine, ameliorates on highfructose (HF) diet-induced metabolic syndrome. Methods SD rats were fed the 60 % HF diet with/without rosiglitazone, and RGPM 100, 300 mg/kg/day, respectively. All groups received regular diet or HF diet, respectively, for 8 weeks. The last three groups treatment of rosiglitazone and RPGM orally for a period of 6 weeks. Results Chronic treatment with RGPM significantly decreased body weight, fat weight and adipocyte size. RGPM significantly prevented the development of the metabolic disturbances such as hypertension, hyperlipidemia and impaired glucose tolerance. RGPM also led to increase in high density lipoprotein level in the HF group. RGPM suppressed high-fructose diet induced vascular inflammation marker expression such as adhesion molecules and ET-1 in aorta as well as increasing of C-reactive protein (CRP) levels in plasma. Similarly, RGPM attenuated hepatic lipid accumulation by inhibition of monocyte chemoattractant protein-1 (MCP-1) expression. Conclusion An administration of RGPM may be a beneficial therapy for the treatment of metabolic syndrome through the improvement of hypertension, obesity, hyperlipidemia, vascular inflammation and insulin resistance.